Global TEC maps based on GNSS data: 1. Empirical background TEC model. Issue 7 (24th July 2013) - Mukhtarov, P.; Pancheva, D.; Andonov, B.; Pashova, L.
Abstract: [1] A global background total electron content (TEC) model is built by using the Center for Orbit Determination of Europe (CODE) TEC data for full 13 years, 1999–2011. It describes the climatological behavior of the ionosphere under both its primary external driver, i.e., the direct photo‐ionization by incident solar radiation, and regular wave particularly tidal forcing from the lower atmosphere. The model construction is based on the very different time scales of the solar cycle, seasonal, and diurnal TEC variabilities (at least an order of magnitude); this leads to modulations of shorter‐period variabilities with periods of the longer ones. Then the TEC spatial‐temporal variability is presented as a multiplication of three separable functions. The solar activity is described by both parameters: F10.7 and its linear rate of change KF while the seasonal variability is presented by sine functions including four subharmonics of the year. The diurnal variability of the TEC model is described by 2D (longitude‐time) sine functions with zonal wave numbers up to 4 and 4 subharmonics of the solar day. The model offers TEC maps which depend on geographic coordinates (5°×5° in latitude and longitude) and UT at given solar activity and day of the year. The presented background model fits to the CODE TEC input data with a zero systematic error and an RMS error of 3.387 TECU. It is able to reproduce the well‐known ionospheric structures as Weddell Sea Anomaly and some longitudinal wave‐like structures. Key Points: Model describes climatological state under forcing from above and below Model is built as a multiplication of three separable functions Model reproduces well WSA and longitudinal wave‐like structures